2022
DOI: 10.1111/cge.14206
|View full text |Cite
|
Sign up to set email alerts
|

The recurrent TCF4 missense variant p.(Arg389Cys) causes a neurodevelopmental disorder overlapping with but not typical for Pitt‐Hopkins syndrome

Abstract: TCF4 haploinsufficiency by deletions, truncating variants or loss‐of‐function missense variants within the DNA‐binding and protein interacting bHLH domain causes Pitt‐Hopkins syndrome (PTHS). This neurodevelopmental disorder (NDD) is characterized by severe intellectual disability (ID), epilepsy, hyperbreathing and a typical facial gestalt. Only few aberrations of the N‐terminus of TCF4 were associated with milder or atypical phenotypes. By personal communication and searching databases we assembled six cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…(Arg389Cys) in exon 15; all with moderate to severe intellectual disability and other features; however, not fulfilling the diagnostic criteria for PTHS (Popp et al, 2022). The underlying mechanism of the phenotypic variability of TCF4-related disorders remains complex and not fully understood at this time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Arg389Cys) in exon 15; all with moderate to severe intellectual disability and other features; however, not fulfilling the diagnostic criteria for PTHS (Popp et al, 2022). The underlying mechanism of the phenotypic variability of TCF4-related disorders remains complex and not fully understood at this time.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, variants affecting the proximal part of the TCF4 gene have been found to produce a milder phenotype of intellectual disability and other nonspecific features (Masson et al, 2022). For instance, Popp et al recently reported a series of six individuals with the de novo variant c.1165C > T, p.(Arg389Cys) in exon 15; all with moderate to severe intellectual disability and other features; however, not fulfilling the diagnostic criteria for PTHS (Popp et al, 2022). The underlying mechanism of the phenotypic variability of TCF4 ‐related disorders remains complex and not fully understood at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about immunologic function, specifically in Pitt–Hopkins syndrome (PTHS), a condition due to either copy number variants at 18q or other variants impacting one T‐cell factor 4 ( TCF4 ) allele. A recurrent missense variant in TCF4 causes a milder phenotype (Popp et al, 2022), and overall, there is variability related to the variant effect (haplosufficiency, dominant negative, and hypomorphic), and 5′ variants can be associated with non‐syndromic developmental delay (Bedeschi et al, 2017). PTHS is thought to have a population frequency of 1:34,000 to 1:41,000 based on chromosomal microarray data (Goodspeed et al, 2018; Zollino et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TCF4 is a protein-coding gene that is located at the long arm of chromosome 18. It encodes the transcription factor 4 (TCF-4) which is expressed in the embryonic central nervous system and plays important roles in neural differentiation and development [5][6][7].…”
mentioning
confidence: 99%
“…[6][7][8] Presence of facial characteristics + additional criteria, either cardinal or supportive, totaling a Score of 6-8. This score warrants TCF4 molecular analysis.…”
mentioning
confidence: 99%